A hybrid damage assessment for E-and S-glass reinforced laminated composite structures under in-plane shear loading. (15th February 2018) - Yilmaz, C.; Akalin, C.; Gunal, I.; Celik, H.; Buyuk, Murat; Suleman, A.; Yildiz, M.
Abstract: Micro-damage initiation and accumulation in two different Glass Fiber Reinforced -E-glass and S-glass- Laminated Composite Structures (LCS) subjected to in-plane shear stressing are monitored with Acoustic Emission (AE) and thermography methods. AE signals caused by micro-damage formation are graphed as a scatter plot of Weighted Peak Frequency (WPF) versus Partial Power 2 (PP2) features and clustered using the K-means algorithm with Bray Curtis dissimilarity function thus resulting in three different well-separated clusters. Each of these clusters corresponds to different micro damages, i.e., transverse cracks, delaminations, or fiber ruptures. It is observed that the E-glass reinforced LCS has higher numbers of AE hits. Thus, the total amount of micro-damage incurred as well as the average temperature change measured by thermography is higher for the E-glass reinforced LCS. It is shown that due to the curing induced residual tensile stress in E-glass reinforced LCS, the initial formation of delamination in E-glass reinforced LCS starts at higher load level. Under the applied shear load, a significant reduction in in-plane shear modulus is observed both for the E-glass and S-glass-reinforced LCS where the E-glass reinforced LCS shows greater reduction. The decrease in in-plane shear modulus is attributed to micro-damage accumulated in the LCS.